Interdisciplinary Domains: Frameworks and Evaluation Criteria - Rahmatollah Fattahi (Iranian Journal of Information Processing & Management, 2024)
The body of interdisciplinary research has become much fatter during the last three decades and a large number of theses, articles, books and even several interdisciplinary journals are published in various fields, including library and information science. There is also a significant tendency among universities to launch interdisciplinary courses and also among Iranian researchers for interdisciplinary studies. Now, doing a thesis with an interdisciplinary approach is a kind of innovation and an academic privilege. However, many researchers, supervisors, graduate students, and reviewers of articles or research projects are not aware of the requirements and frameworks of interdisciplinary research and, as a result, the evaluation methods of such studies. Compared to books and articles related to the evaluation of interdisciplinary studies in English that present various frameworks and methods, we lack examples in Persian language in this field. In this article, in the form of conceptual research method and by reviewing some related articles and books in Persian and English, a specific framework and criteria for evaluating interdisciplinary research based on the main and conventional parts of a research article have been introduced. Based on this, sections such as title, abstract, keywords, theoretical foundations, objectives, statement of the problem, questions or hypotheses, research background, methodology, findings, conclusions, and cited sources can be evaluated based on criteria. One can use this framework to identify concrete examples to check the extent to which researchers pay attention to interdisciplinary frameworks and approaches. The frameworks and criteria introduced in this article are useful for researchers, supervisors, students and referees of theses or scientific articles, including in the field of library and information science.